2018
DOI: 10.1111/jgh.13902
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cardiac troponin T in cirrhotic patients with emergency care admissions: Associations with mortality

Abstract: A large proportion of cirrhotic patients in the ED have elevated levels of cTnT even if there is no evidence of cardiac disease. Elevated cTnT is associated with increased mortality during 1 year after correcting for Model for End-stage Liver Disease and CLIF-C-ACLF scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Previously published series have reported that abnormally elevated pretransplant troponin levels were associated with a higher risk of posttransplant cardiac events and mortality in single-center LT populations. [12][13][14] These observations suggest that pretransplant troponin isoform testing may be an attractive pretransplant test for the detection of underlying cardiac risk in LT patients.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Previously published series have reported that abnormally elevated pretransplant troponin levels were associated with a higher risk of posttransplant cardiac events and mortality in single-center LT populations. [12][13][14] These observations suggest that pretransplant troponin isoform testing may be an attractive pretransplant test for the detection of underlying cardiac risk in LT patients.…”
mentioning
confidence: 95%
“…Elevated troponin levels have also been reported in cohorts of patients with cirrhosis and acute liver failure and are prognostic for adverse outcomes, including in LT populations. [12][13][14][15] Occult elevations in cardiac troponin appear to be associated with cirrhotic cardiomyopathy (CCM), a spectrum of cardiac abnormalities related to underlying advanced liver disease. The CCM diagnosis includes abnormal troponin as one of the supporting diagnostic criteria.…”
mentioning
confidence: 99%
“…Further studies have suggested that elevated troponin values occur in critically ill patients without initial cardiac disease and have a negative impact on prognosis, albeit not as an independent prognostic factor [ 9 , 10 ]. Moreover, in a trial from 1976, more than 90% of ALF patients examined showed cardiac abnormalities, 25% of whom suffered sudden cardiac death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we performed emergent coronary arteriography showing no luminal narrowing. Finally, we determined that acute decompensation of liver cirrhosis with a hyperdynamic state after total hip arthroplasty [ 4 , 5 ] led to an increase in serum hs-cTnI levels [ 6 ] and ECG changes due to Aslanger’s sign ( Fig. 1 ).…”
mentioning
confidence: 99%